Reaction, crystallization and element migration in coal slag melt during isothermal molten process. (1st March 2017) - Shen, Zhongjie; Hua, Xin; Liang, Qinfeng; Xu, JianLiang; Han, Dong; Liu, Haifeng
Highlights: Coal slag crystallization behavior during isothermal molten process was observed. Crystal formed in molten slag and varied with slag molten temperatures. Crystal size first increased and then remained stable with increasing molten time. Elements performed varied enrichment characteristics during crystallization. Alkali metal element had strong migration features in crystal and amorphous phase. Abstract: Crystallization behavior of coal slag influences the slag flow and rheology properties in the slagging gasifier. Crystallization behavior of coal slag during isothermal molten process was observed and analyzed on the in situ experiment study. Complex aluminosilicates reaction led crystal to separate out in molten slag, mainly including the hexahedral crystal and acicular crystal, which varied with slag molten temperatures. The growth of crystal size first increased and then remained stable on molten slag surface with increasing isothermal time. The distribution and migration of coal slag elements on slag surface and inside crystal were also detected by time of flight secondary ion mass spectrometry (ToF-SIMS). Al, Ca and Si homogeneously distributed on the crystal and amorphous phase, due to the high content of element in coal slag. K mainly enriched on the crystal surface and amorphous phase while Na diffused and migrated onto the crystal surface. Mg doped into the interior of crystal, and the distribution of Fe varied with crystal type.